Schooling as Pathogenic: Exploring the Destructive Implications of Globalist Educational Reform - Michael D. Berry (Canadian Society for Studies in Education, 2008)
The majority of formal schooling, this article contends, is pathogenic. Globalist educational reforms, such as UNESCO's Education for All initiative, create pathological subjectivities through socialization. Drawing on Durkheim and Bourdieu's work, which presents formal education as a conservative institution that sustains privilege and maintain the status quo through socialization, this article explores the implications of schools' socializing function. Globalized education, theorized according to Loomba's work on the colonialist/postcolonialist functions of power and privilege, is a form of colonialism, dictated by neoliberal elites. By implication, this article argues a basic form of systemic violence consists in schools, globally. Drawing on Harber's paradigm of the school as violence, the article contends that education actively fosters institutional and subjective violence on a global level, by engendering self-entitled, consumerist identities in privileged students in the global North, and obedient labourers in the global South.